Mesoporous crystal phase / amorphous phase hollow g-C3N4 photocatalyst and preparation method thereof
By using large pore size MSNs as hard templates, the hollow g-C3N4 photocatalysts of mesoporous crystal phase/amorphous phase are prepared, and the problems of small specific surface area and strict preparation conditions in the prior art are solved, thereby achieving efficient visible light absorption and utilization.
Patent Information
- Application Number
- CN202411587267.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-25
AI Technical Summary
In the prior art, the specific surface area of the graphite phase carbon nitride (g-C3N4) photocatalyst is low, resulting in limited utilization efficiency of visible light and harsh preparation conditions, making it difficult to obtain a homozygous junction with ideal results.
Mesoporous silica nanoparticles (MSNs) with large pore sizes were used as hard templates to prepare mesoporous crystal phase/amorphous phase hollow g-C3N4 photocatalysts by thermal polymerization, increasing their specific surface area and introducing rich mesoporous structures.
The specific surface area and light response ability of g-C3N4 are improved, and its absorption and utilization efficiency of visible light is enhanced. The preparation method is simple and controllable, and the product dispersibility is good.
Smart Images

Figure CN119500220A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of semiconductors, and in particular relates to a mesoporous crystalline phase / amorphous phase hollow g-C3N4 photocatalyst and a preparation method thereof. Background Art
[0002] Graphitic carbon nitride (g-C3N4) is a two-dimensional layered semiconductor material with good thermodynamic stability and is an excellent photocatalytic material. In addition, its raw materials are simple and easy to obtain, the preparation conditions are low, and the experimental repeatability is good, so it is widely used in the field of photocatalysis. However, when directly using nitrogen-containing precursors such as melamine, dicyandiamide or urea, the g-C3N4 prepared has a low specific surface area and limited efficiency in utilizing visible light. In order to further improve the photocatalytic performance of g-C3N4, researchers have developed a variety of methods. Currently, there are four main methods used: (1) element doping, (2) construction of hetero / homojunctions, (3) modification of co-catalysts, and (4) morphology and structure regulation.
[0003] The element doping method mainly uses the doping energy level as a charge capture trap to improve the utilization rate of photogenerated carriers. The electronic structure of g-C3N4 can be adjusted by doping with metal elements or non-metal elements to broaden its visible light absorption range. Common doped non-metal elements include O, S, P, B, C, I and F, among which O, S, and P can replace the Nu atom in the triazine ring, while the C atom can replace the bridging carbon atom, and the O element can form an oxygen-containing functional group to improve the photocatalytic performance. In addition, the synergistic effect of different non-metal elements can also improve the photocatalytic performance, such as P and S, P and O, B and S elements, etc. The surface modification of g-C3N4 with metal elements can change its charge distribution, thereby improving the migration efficiency of photogenerated carriers and increasing photon absorption, such as Pt, Ni, Fe, Ce and Cu. However, the amount of doping elements is a key issue that needs to be paid attention to. Multiple sets of variables need to be designed when preparing the catalyst, and the hydrogen production efficiency is very limited (~1.5 molh -1 g -1 ).
[0004] Constructing a heterojunction is the most commonly used method to promote the effective separation of electrons and holes. There are four common heterojunctions, namely type I, type II, type Z and type S. For example, the g-C3N4 / TiO2 heterojunction can be obtained by mixing urea and TiCl4 at 150°C for crystallization, but too little g-C3N4 or TiO2 will lead to a decrease in photocatalytic ability, so regulating their ratio is also the key in the synthesis. However, studies have shown that the morphology of the synthesized g-C3N4 / TiO2 will also affect its catalytic performance. When an appropriate amount of V is doped in g-C3N4 / TiO2, the prepared g-C3N4 / V@TiO2 can also improve the absorption range of visible light. In short, when constructing a heterojunction, it is necessary to consider many factors such as selecting a suitable second component material, controlling the morphology and size of the heterojunction, and optimizing the interface contact between the two materials. Therefore, researchers have developed a series of methods to avoid the above problems, such as using different carbon nitride phases to form a homojunction. However, the homojunction currently prepared by mixed calcination of crystalline phase and amorphous phase has the problem of difficult-to-control growth. The ratio of different phases needs to be strictly controlled during multi-step calcination. The preparation conditions are harsh, and it is difficult to obtain an ideal homojunction.
[0005] Studies have shown that introducing a porous structure and increasing the specific surface area is an effective way to enhance the light response ability. However, there are few studies on the use of mesoporous silica nanoparticles (MSNs) with rich mesoporous structures as hard templates and the preparation of g-C3N4 by a simple thermal polymerization method, and its development is very slow. Summary of the invention
[0006] In order to solve the above-mentioned technical problems, the present invention provides a mesoporous crystalline / amorphous hollow g-C3N4 photocatalyst and a preparation method thereof, and adopts large-pore MSNs as a hard template, which is beneficial to increase the specific surface area of g-C3N4, introduce rich mesoporous structure and form hollow g-C3N4.
[0007] The present invention provides a method for preparing a mesoporous crystalline phase / amorphous phase hollow g-C3N4 photocatalyst, and the preparation method specifically comprises the following steps:
[0008] S1, mixing water, cationic surfactant, ethanol and catalyst in proportion to obtain a mixed solution;
[0009] S2, heating the mixed solution to 60-80°C while stirring, adding tetraethyl orthosilicate, stirring for 2h, and cooling to room temperature after the reaction to obtain a white precipitate;
[0010] S3, mixing the white precipitate with ethanol and ammonium chloride in proportion to obtain a mixture, subjecting the mixture to hydrothermal reaction, centrifugation, washing, drying, and then removing the surfactant to obtain large-pore MSNs;
[0011] S4, uniformly mixing MSNs, melamine and urea and then subjecting them to carbonization treatment to obtain g-C3N4 powder;
[0012] S5. Wash the g-C3N4 powder in an HF solution and dry it to obtain a mesoporous crystalline / amorphous hollow g-C3N4 photocatalyst.
[0013] Compared with the prior art, the present invention uses self-developed large-pore mesoporous silica nanoparticles (MSNs) as a hard template, which is beneficial to increasing the specific surface area of g-C3N4, introducing rich mesoporous structures and forming hollow g-C3N4, and proposing a simple and controllable synthesis system to prepare mesoporous crystalline phase / amorphous phase hollow g-C3N4 with good dispersion, which is of great significance for the design and synthesis of g-C3N4 and the development of photocatalytic systems based on g-C3N4.
[0014] In some embodiments, the mass ratio of cationic surfactant: water: ethanol: catalyst: tetraethyl orthosilicate is 1:480: (38-85): 3.5: (4.7-4.8).
[0015] Compared with the prior art, the present invention adopts ethanol as a co-solvent to slow down the reaction rate of the synthesis system, which is beneficial to controlling the size and morphology of the final product.
[0016] In some embodiments, in step S1, the cationic surfactant is hexadecyltrimethylammonium bromide, and the molecular weight is 364.
[0017] In some embodiments, in step S1, the catalyst is NaOH, and is analytically pure.
[0018] In some embodiments, in step S3, the parameters of the hydrothermal reaction are as follows: temperature is 140-170° C., and time is 24-48 h.
[0019] In some embodiments, in step S3, the surfactant is removed by calcination, and the calcination parameters are as follows: calcination temperature is 450-600°C, calcination time is 3-5h, and heating rate is 1-2°C / min.
[0020] In some embodiments, in step S4, the mass ratio of MSNs, melamine and urea is 1:(1-3):(1-3).
[0021] Compared with the prior art, the present invention uses melamine and urea as nitrogen-rich precursors, and utilizes the interaction between melamine and the abundant silanol (Si-OH) on the surface of silica to reduce the temperature (about 40°C) at which melamine is heated and polymerized into g-C3N4. In addition, silica can inhibit the sublimation of melamine and promote its polymerization. The hydrogen bonds in Si-OH can pull the urea in the melamine molecules. 2 The lone pair of electrons on the N atom makes 2 The N atom has a positive charge and weakens 2 N- 1 H bond, which is beneficial to the removal of NH3 molecules.
[0022] In addition, the mesoporous channels of MSNs have an enrichment effect on melamine and can promote its polymerization. Melamine first thermally migrates and deposits on the surface of the MSNs channel. Then, under the strong interaction between melamine and mesoporous silica, the sublimation process of melamine is inhibited, effectively avoiding the formation of bulk g-C3N4. This is a new green synthesis technology.
[0023] In some embodiments, in step S4, the parameters of the carbonization treatment are as follows: a heating rate of 10-15°C / min, an inert gas as the protective gas, a temperature of 500-550°C, and a time of 3-6h.
[0024] The present invention also provides a mesoporous crystalline phase / amorphous phase hollow g-C3N4 photocatalyst, which is prepared by the above preparation method.
[0025] In some embodiments, the mesoporous crystalline / amorphous hollow g-C3N4 photocatalyst has a cavity size of 42-62 nm, a shell thickness of 32-54 nm, and a particle size of 90-115 nm.
[0026] Compared with the prior art, the present invention uses two nitrogen-rich precursors as carbon sources for the first time and uses large-pore MSNs as hard templates to synthesize homojunction carbon nitride nanomaterials with hollow structures. The method is simple, easy to operate, has good repeatability, and has uniform size distribution. In addition, the homojunction carbon nitride material can also be compounded with other substances to further improve properties such as photocatalysis, showing application potential in many fields such as photocatalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a high-resolution transmission electron microscopy (HRTEM) photograph of the mesoporous crystalline / amorphous hollow g-C3N4 photocatalyst prepared in Example 1 of the present invention;
[0028] Figure 2 This is a SEM image of the mesoporous crystalline / amorphous hollow g-C3N4 photocatalyst prepared in Example 1 of the present invention;
[0029] Figure 3 XRD curves of the mesoporous crystalline / amorphous hollow g-C3N4 photocatalyst prepared in Example 1 of the present invention, the sample prepared in Comparative Example 1, and the sample prepared in Comparative Example 2;
[0030] Figure 4 This is a small-angle XRD scattering curve of the mesoporous crystalline / amorphous hollow g-C3N4 photocatalyst prepared in Example 1 of the present invention;
[0031] Figure 5 This is a comparison chart of the visible light catalytic water decomposition and hydrogen production performance of the mesoporous crystalline phase / amorphous hollow g-C3N4 photocatalysts prepared in Examples 1 to 6 of the present invention, the sample prepared in Comparative Example 1, and the sample prepared in Comparative Example 2. DETAILED DESCRIPTION
[0032] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.
[0033] It should be noted that the endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.
[0034] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.
[0035] The technical effects of the present invention are described below in conjunction with specific embodiments.
[0036] It should be noted that in the embodiments of the present invention, the raw materials used are:
[0037] Cationic surfactant CTAB, analytical grade, Sigma-Aldrich;
[0038] Tetraethoxysilane (TEOS) relative density 0.93, analytical grade, Sinopharm Chemical Reagent Co., Ltd.;
[0039] Melamine, 99%, Aladdin;
[0040] Urea, analytical grade, Aladdin;
[0041] Sodium hydroxide, analytical grade, was purchased from Sinopharm Chemical Reagent Co., Ltd.
[0042] Example 1
[0043] The present embodiment provides a mesoporous crystalline phase / amorphous hollow g-C3N4 photocatalyst, which is prepared by the following preparation method: cationic surfactant: water: ethanol: catalyst: silicon source = mass ratio of 1:480:85:3.5:4.7, 0.4g CTAB, 33.89g ethanol, 1.4g 2M sodium hydroxide and 192g water are mixed and stirred at 80°C, 1.89g TEOS is added, and the reaction is carried out for 2h. Then the reactants are cooled to room temperature and centrifuged, and the centrifuged product: ethanol: ammonium chloride are mixed in a mass ratio of 1:1:0.02, and hydrothermal at 140°C for 24h. Finally, centrifugal washing with deionized water, drying, and calcination, calcination conditions: 550°C, 4h, heating rate of 1.5°C·min -1 , and large-pore MSNs were obtained. MSNs, melamine and urea were mixed in a mass ratio of 1:1:1 and carbonized in an argon atmosphere under the following carbonization conditions: heating rate of 10℃ / min, temperature of 550℃, and time of 3h. The obtained light yellow powder was washed with 10% HF solution and dried to obtain hollow g-C3N4, named E13-C3N4-HF.
[0044] Example 2
[0045] The present embodiment provides a mesoporous crystalline phase / amorphous hollow g-C3N4 photocatalyst, which is prepared by the following preparation method: cationic surfactant: water: ethanol: catalyst: silicon source = mass ratio of 1:480:0:3.5:4.7, 0.4g CTAB, 1.4g 2M sodium hydroxide and 192g water are mixed and stirred at 80°C, 1.89g TEOS is added, and the reaction is carried out for 2h. Then the reactants are cooled to room temperature and centrifuged, and the centrifuged product: ethanol: ammonium chloride are mixed in a mass ratio of 1:1:0.02, and hydrothermal at 140°C for 24h. Finally, centrifugal washing with deionized water, drying, and calcination, calcination conditions: 550°C, 4h, heating rate of 1.5°C·min -1, and large-pore MSNs were obtained. MSNs, melamine and urea were mixed in a mass ratio of 1:1:1 and carbonized in an argon atmosphere under the following carbonization conditions: heating rate of 10℃ / min, temperature of 550℃, and time of 3h. The obtained light yellow powder was washed with 10% HF solution and dried to obtain hollow g-C3N4, named E0-C3N4-HF.
[0046] Example 3
[0047] The present embodiment provides a mesoporous crystalline phase / amorphous hollow g-C3N4 photocatalyst, which is prepared by the following preparation method: cationic surfactant: water: ethanol: catalyst: silicon source = mass ratio of 1:480:53:3.5:4.7, 0.4g CTAB, 33.89g ethanol, 1.4g 2M sodium hydroxide and 192g water are mixed and stirred at 80°C, 1.89g TEOS is added, and the reaction is carried out for 2h. Then the reactants are cooled to room temperature and centrifuged, and the centrifuged product: ethanol: ammonium chloride are mixed in a mass ratio of 1:1:0.02, and hydrothermal at 140°C for 24h. Finally, centrifugal washing with deionized water, drying, and calcination, calcination conditions: 550°C, 4h, heating rate of 1.5°C·min -1 , and large-pore MSNs were obtained. MSNs, melamine and urea were mixed in a mass ratio of 1:1:1 and carbonized in an argon atmosphere under the following carbonization conditions: heating rate of 10℃ / min, temperature of 550℃, and time of 3h. The obtained light yellow powder was washed with 10% HF solution and dried to obtain hollow g-C3N4, named E10-C3N4-HF.
[0048] Example 4
[0049] The present embodiment provides a mesoporous crystalline phase / amorphous hollow g-C3N4 photocatalyst, which is prepared by the following preparation method: cationic surfactant: water: ethanol: catalyst: silicon source = mass ratio of 1:480:53:3.5:4.7, 0.4g CTAB, 33.89g ethanol, 1.4g 2M sodium hydroxide and 192g water are mixed and stirred at 80°C, 1.89g TEOS is added, and the reaction is carried out for 2h. Then the reactants are cooled to room temperature and centrifuged, and the centrifugal product: ethanol: ammonium chloride are mixed in a mass ratio of 1:1:0.02, and hydrothermal at 170°C for 24h. Finally, centrifugal washing with deionized water, drying, and calcination, calcination conditions: 550°C, 4h, heating rate of 1.5°C·min -1, and large-pore MSNs were obtained. MSNs, melamine and urea were mixed in a mass ratio of 1:1:1 and carbonized in an argon atmosphere under the following carbonization conditions: heating rate of 10℃ / min, temperature of 550℃, and time of 3h. The obtained light yellow powder was washed with 10% HF solution and dried to obtain hollow g-C3N4, named E10-170-C3N4-HF.
[0050] Example 5
[0051] The present embodiment provides a mesoporous crystalline phase / amorphous hollow g-C3N4 photocatalyst, which is prepared by the following preparation method: cationic surfactant: water: ethanol: catalyst: silicon source = mass ratio of 1:480:53:3.5:4.7, 0.4g CTAB, 33.89g ethanol, 1.4g 2M sodium hydroxide and 192g water are mixed and stirred at 80°C, 1.89g TEOS is added, and the reaction is carried out for 2h. Then the reactants are cooled to room temperature and centrifuged, and the centrifuged product: ethanol: ammonium chloride are mixed in a mass ratio of 1:1:0.005, and hydrothermal at 170°C for 24h. Finally, centrifugal washing with deionized water, drying, and calcination, calcination conditions: 550°C, 4h, heating rate of 1.5°C·min -1 , and large-pore MSNs were obtained. MSNs, melamine and urea were mixed in a mass ratio of 1:1:1 and carbonized in an argon atmosphere under the following carbonization conditions: heating rate of 10℃ / min, temperature of 550℃, and time of 3h. The obtained light yellow powder was washed with 10% HF solution and dried to obtain hollow g-C3N4, named E10-0.005N-C3N4-HF.
[0052] Embodiment 6:
[0053] The present embodiment provides a mesoporous crystalline phase / amorphous hollow g-C3N4 photocatalyst, which is prepared by the following preparation method: cationic surfactant: water: ethanol: catalyst: silicon source = mass ratio of 1:480:85:3.5:4.7, 0.4g CTAB, 33.89g ethanol, 1.4g 2M sodium hydroxide and 192g water are mixed and stirred at 80°C, 1.89g TEOS is added, and the reaction is carried out for 2h. Then the reactants are cooled to room temperature and centrifuged, and the centrifuged product: ethanol: ammonium chloride are mixed in a mass ratio of 1:1:0.02, and hydrothermal at 140°C for 24h. Finally, centrifugal washing with deionized water, drying, and calcination, calcination conditions: 550°C, 4h, heating rate of 1.5°C·min -1, and large-pore MSNs were obtained. MSNs, melamine and urea were mixed in a mass ratio of 1:1:1 and carbonized in an argon atmosphere under the following carbonization conditions: heating rate of 10℃ / min, temperature of 550℃, and time of 3h. The obtained light yellow powder was washed with 10% HF solution and dried to obtain hollow g-C3N4, named E15-C3N4-HF.
[0054] Comparative Example 1
[0055] This comparative example provides a sample, which is prepared by the following preparation method: melamine and urea are mixed in a mass ratio of 1:1, and carbonized in an argon atmosphere. The carbonization conditions are: a heating rate of 10°C / min, a temperature of 550°C, and a time of 3h. The obtained g-C3N4 is named M1U1.
[0056] Comparative Example 2
[0057] This comparative example provides a sample, which is prepared by the following preparation method: melamine is carbonized in an argon atmosphere, and the carbonization conditions are: a heating rate of 10°C / min, a temperature of 550°C, and a time of 3h. The obtained g-C3N4 is named Me.
[0058] The performance of the mesoporous crystalline / amorphous hollow g-C3N4 photocatalysts prepared in Examples 1 to 6, the samples prepared in Comparative Example 1 and the samples prepared in Comparative Example 2 were tested. The test results are as follows: Figure 1-Figure 5 As shown, Figure 1 This is a high-resolution transmission electron microscopy (HRTEM) photograph of the mesoporous crystalline / amorphous hollow g-C3N4 photocatalyst prepared in Example 1 of the present invention; Figure 1 It can be seen that the mesoporous crystalline / amorphous hollow g-C3N4 photocatalyst prepared in Example 1 has a composite structure of crystalline and amorphous phases.
[0059] Figure 2 The SEM image of the mesoporous crystalline / amorphous hollow g-C3N4 photocatalyst prepared in Example 1 of the present invention; Figure 2 It can be seen that the mesoporous crystalline / amorphous hollow g-C3N4 photocatalyst prepared in Example 1 has a uniform particle size distribution and an average particle size of 145 nm, and obvious mesopores and the formation of a hollow structure can be observed on the particle surface.
[0060] Figure 3 The XRD curves of the mesoporous crystalline / amorphous hollow g-C3N4 photocatalyst prepared in Example 1 of the present invention, the sample prepared in Comparative Example 1 and the sample prepared in Comparative Example 2 are shown in FIG. Figure 3It can be seen that the crystallinity of the mesoporous crystalline / amorphous hollow g-C3N4 photocatalyst prepared in Example 1 and the sample prepared in Comparative Example 1 are not as high as that of the sample prepared in Comparative Example 2, indicating that the mesoporous crystalline / amorphous hollow g-C3N4 photocatalyst prepared in Example 1 and the sample prepared in Comparative Example 1 are both C3N4 composited with crystalline and amorphous phases, wherein the diffraction peaks of 13° and 27.3° are respectively attributed to the structural unit (100) and the diffraction peak (002) of the layered stacking structure.
[0061] Figure 4 The small-angle XRD scattering curve of the mesoporous crystalline / amorphous hollow g-C3N4 photocatalyst prepared in Example 1 of the present invention is shown in FIG. Figure 4 It can be seen that the mesoporous crystalline / amorphous hollow g-C3N4 photocatalyst prepared in Example 1 is a disordered structure, but there are two broad peaks, reflecting the polydispersity of the structure, that is, there are a variety of microstructures of different shapes or sizes in the sample, and the scattering signals of these structures are superimposed to form a broad scattering peak, indicating that there are pore structures of various sizes in the synthesized sample, which is beneficial to enhance the absorption and utilization efficiency of light.
[0062] Figure 5 This is a comparison chart of the visible light catalytic water decomposition and hydrogen production performance of the mesoporous crystalline phase / amorphous hollow g-C3N4 photocatalysts prepared in Examples 1 to 6 of the present invention, the samples prepared in Comparative Example 1, and the samples prepared in Comparative Example 2; Figure 5 It can be seen that the hydrogen production efficiency of the mesoporous crystalline / amorphous hollow g-C3N4 photocatalyst prepared by the present invention is higher than the hydrogen production performance of g-C3N4 (Me and M1U1) prepared without using MSNs as hard template in the comparative example, and is more than 21 times of its hydrogen production efficiency, reaching up to 3.21mmolg -1 h -1 (802 times that of ordinary g-C3N4).
[0063] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A method for preparing a mesoporous crystalline / amorphous hollow g-C3N4 photocatalyst, characterized in that: The preparation method specifically comprises the following steps: S1, mixing water, cationic surfactant, ethanol and catalyst in proportion to obtain a mixed solution; S2, heating the mixed solution to 60-80°C while stirring, adding tetraethyl orthosilicate, stirring for 2h, and cooling to room temperature after the reaction to obtain a white precipitate; S3, mixing the white precipitate with ethanol and ammonium chloride in proportion to obtain a mixture, subjecting the mixture to hydrothermal reaction, centrifugation, washing, drying, and then removing the surfactant to obtain large-pore MSNs; S4, uniformly mixing MSNs, melamine and urea and then subjecting them to carbonization treatment to obtain g-C3N4 powder; S5. Wash the g-C3N4 powder in an HF solution and dry it to obtain a mesoporous crystalline / amorphous hollow g-C3N4 photocatalyst.
2. The preparation method according to claim 1, characterized in that The mass ratio of cationic surfactant: water: ethanol: catalyst: tetraethyl orthosilicate is 1:480:(38-85): 3.5:(4.7-4.8)。 3. The preparation method according to claim 1, characterized in that: In the step S1, the cationic surfactant is hexadecyltrimethylammonium bromide, and the molecular weight is 364.
4. The preparation method according to claim 1, characterized in that: In step S1, the catalyst is NaOH, and is analytically pure.
5. The preparation method according to claim 1, characterized in that: In step S3, the parameters of the hydrothermal reaction are as follows: temperature is 140-170° C., and time is 24-48 hours.
6. The preparation method according to claim 1, characterized in that: In step S3, the surfactant is removed by calcination, and the calcination parameters are as follows: calcination temperature is 450-600°C, calcination time is 3-5h, and heating rate is 1-2°C / min.
7. The preparation method according to claim 1, characterized in that: In the step S4, the mass ratio of MSNs, melamine and urea is 1:(1-3):(1-3).
8. The preparation method according to claim 1, characterized in that: In step S4, the parameters of the carbonization treatment are as follows: the heating rate is 10-15°C / min, the protective gas is an inert gas, the temperature is 500-550°C, and the time is 3-6h.
9. A mesoporous crystalline / amorphous hollow g-C3N4 photocatalyst, characterized in that: The method is prepared by any one of claims 1 to 8.
10. The mesoporous crystalline / amorphous hollow g-C3N4 photocatalyst according to claim 9, characterized in that: The cavity size of the mesoporous crystalline / amorphous hollow g-C3N4 photocatalyst is 42-62nm, the shell thickness is 32-54nm, and the particle size is 90-115nm.